Pengukuran Medan Magnet Lemah Menggunakan Sensor Magnetik Fluxgate dengan Satu Koil Pick-Up - Mitra Djamal; Rahmondia Nanda Setiadi (Institute for Research and Community Services (LPPM) ITB, 2006)
A magnetic sensor has been developed for measuring a very low magnetic field. The sensor consists of two primary coils (excitation coil) and one secondary coil (pick-up coil). Primary coil that wound at ferromagnetic core is made symmetry each other. Whereas secondary coil is wound to both of cores. Primary coil drives the core until it saturated. The generated magnetic field from excitation have the contrary direction, so if there is no external magnetic field, the magnetic field inside the secondary coil is symmetry, but if there is an external magnetic field, there will be magnetic field changes inside secondary coil. These changes will induce secondary coil, as a consequence, there will be an induction voltage that acts as signal at the ends of secondary coil. The signal is then differentiated, amplified, inserted to controlled rectifier, integrated, and amplified for the last time. From measurement results, it can be obtained that magnetic sensor can measure magnetic field in the range of measurement from -40 Î¼T to 40 Î¼T, with sensitivity about 346.47 mV/Î¼T and relative error less than 4%.